Work Discipline and Competency of the Democracy Volunteer of Makassar City in General Election 2019 - Mustafa, Delly; Niswaty, Risma; Botutihe, Nuzlan (Journal of Public Representative and Society Provision, 2022)
This study evaluates the impact of work discipline and competence on the performance of the Makassar City Volunteer Democracy during the 2019 General Election, focusing on both individual and combined contributions. Using a quantitative approach, multiple regression analysis was conducted to explore these relationships. Data were collected from volunteers through structured questionnaires and analyzed with SPSS.21, employing correlation coefficients, T-tests, F-tests, and R-Square. Results indicate a significant positive relationship between work discipline (β=0.262 = 0.262β=0.262) and competence (β=0.579 = 0.579β= 0.579) with performance, with a combined effect explaining 57.4% of the variance in volunteer performance.